Syndromic (phenotypic) diarrhoea of infancy/tricho-hepato-enteric syndrome. Issue 1 (9th October 2013) - Fabre, Alexandre; Breton, Anne; Coste, Marie-Edith; Colomb, Virginie; Dubern, Beatrice; Lachaux, Alain; Lemale, Julie; Mancini, Julien; Marinier, Evelyne; Martinez-Vinson, Christine; Peretti, Noel; Perry, Ariane; et al.
Abstract : Objectives: Syndromic diarrhoea/tricho-hepato-enteric syndrome (SD/THE) is a rare congenital syndrome. The main features are intractable diarrhoea of infancy, hair abnormalities, facial dysmorphism, intrauterine growth restriction and immune system abnormalities. It has been linked to abnormalities in two components of the putative human ski complex: SKIV2L and TTC37. The long-term outcome of this syndrome is still unknown. We aim to describe the long-term outcome, in the French cohort of patients born since 1992. Design: Review of the clinical and biological features of the 15 patients with SD/THE, followed in France and born between 1992 and 2010. Results: All patients presented typical SD/THE syndrome features, of intractable diarrhoea in infancy requiring parenteral nutrition, a facial dysmorphism with hair abnormalities, and immunological disorders. Half of them also had liver and skin abnormalities. Five children died, among which 3 died due to infections. Probabilities of survival according to the Kaplan-Meier method were 93.3%, 86.7%, 74.3 and 61.9%, respectively at 1 year, 5 years, 10 years and 15 years of age. 3/15 were weaned from parenteral nutrition (PN) with likelihood of weaning being 10% at 5 years and 40% at 10 years. At birth 80% were small for gestational age and the short stature persisted in 60%. Haemophagocytic syndrome was noted in 60% and mild mental retardation was present in 60%. Conclusions: SD/THE is a rare disease with high morbidity and mortality. Management should be focused on nutrition and immunological defects.